2002
DOI: 10.1007/s100380200002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutations in the arginine vasopressin receptor 2 gene causing nephrogenic diabetes insipidus in Chinese patients

Abstract: Congenital nephrogenic diabetes insipidus (NDI) is, in most instances, a rare X-linked recessive renal disorder (MIM 304800) characterized by the clinical symptoms of polyuria, polydipsia, and dehydration. The X-linked NDI is associated with mutations of the arginine vasopressin receptor type 2 (AVPR2) gene, which results in resistance to the antidiuretic action of arginine vasopressin (AVP) in the renal tubules and collecting ducts. Identification of mutations in the AVPR2 gene can facilitate early diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…Two patients with p.R106C reported by Pasel et al [ 14 ] had high basal urine osmolality and partial response to AVP administration. Chen et al [ 15 ] also reported that an NDI patient with p.R106C had normal urine and plasma osmolality and plasma electrolytes, similar to our patient (Case 2).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Two patients with p.R106C reported by Pasel et al [ 14 ] had high basal urine osmolality and partial response to AVP administration. Chen et al [ 15 ] also reported that an NDI patient with p.R106C had normal urine and plasma osmolality and plasma electrolytes, similar to our patient (Case 2).…”
Section: Discussionsupporting
confidence: 84%
“…The mutations p.K100KfsX91 and p.W99X produced a premature stop codon, resulting in a truncated protein. Regarding p.R106C, that mutation was identified in 7.7% (5/65) of Japanese NDI patients [ 17 ] and also was identified in other Asian and ethnic populations [ 2 , 12 , 15 , 16 ]. The p.R106C mutation occurs at CpG nucleotides, which are mutation hot spots for genetic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, only 7 mutations causing partial NDI have been previously reported [7,8,9,10,11,12,13]. Most AVPR2 mutations are missense mutations that disrupt receptor function at various levels, such as intracellular receptor retention, defects in ligand binding or defects in G protein coupling and activation [14].…”
Section: Introductionmentioning
confidence: 99%
“…NDI manifests in three forms, namely X-linked, autosomal dominant, and autosomal recessive [88]. X-linked NDI is due to mutations in the arginine vasopressin 2 receptor, which initiates hAQP2 expression and trafficking to the plasma membrane when bound to arginine vasopressin [89][90][91][92]. Autosomal NDI is due to point mutations in hAQP2.…”
Section: Introductionmentioning
confidence: 99%